The Coinage of Kalynda - Ömer Tatar (Gephyra)
This study discusses the coinage of Kalynda, the exact location of whose polis centre remains uncertain. Located near the Karian-Lycian border, Kalynda probably struck civic coins beginning in the 1st century BC. The coinage of the city includes three bronze series. The minting place of a series of silver coins previously attributed to Kalynda remains debated. The bronze coins predominantly depict Artemis and symbols associated with the goddess, indicating her importance in the city. The iconographic similarities between Kalynda’s coins and those of other Karian and Lycian cities, particularly the Lycian League, suggest that Kalynda’s coinage may have been influenced by regional trends. While the exact dating of these coins is still under discussion, Kalynda probably began striking civic coins in the first quarter of the 1st century BC. The absence of Kalyndan coins in archaeological finds from Şerefler/Asar Tepe, which is thought to have remained on the territory of Kalynda, raises questions about the location and numismatic history of the city.